2016
DOI: 10.1038/srep27712
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization and magneto-transport staircaselike behavior in layered perovskite Sr2CoO4 at low temperature

Abstract: Polycrystalline layered perovskite Sr2CoO4 sample was synthesized by high temperature and high pressure method. The staircaselike behavior has been observed in the magnetization and resistivity versus field curves of Sr2CoO4 at low temperature. The main features of the steps can be obtained from the measured results: (i) the positions of the external magnetic field at which steps occur are varying in different measurement runs, (ii) the steps only appear at low temperature and disappear with a slight increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Their results are further supported by the simulations studies of simple Ising Hamiltonian with in-plane ferromagnetic interactions and randomly mixed off-plane interactions [77,78]. Likewise, Li et al [79] reported that the staircase-like behavior observed in the M-H curves at low temperature in layered perovskite Sr 2 CoO 4 is due to the avalanche of flipping domains in terms of the random field theory.…”
Section: Composition and Temperature Dependence Of Hysteresis Loop Pa...mentioning
confidence: 72%
“…Their results are further supported by the simulations studies of simple Ising Hamiltonian with in-plane ferromagnetic interactions and randomly mixed off-plane interactions [77,78]. Likewise, Li et al [79] reported that the staircase-like behavior observed in the M-H curves at low temperature in layered perovskite Sr 2 CoO 4 is due to the avalanche of flipping domains in terms of the random field theory.…”
Section: Composition and Temperature Dependence Of Hysteresis Loop Pa...mentioning
confidence: 72%
“…[17][18][19][20][21][22] With further reduction, BM SrFeO2.5 films could transform to infinite-layer SrFeO2 SP phase. [21,23] However, in the cobaltite system, further reduction of BM SrCoO2.5 films led to amorphous films or nano-twinned, tetrahedrally-coordinated phases [22,24] rather than the formation of SrCoO2 SP phase or even the Sr2CoO4 [25,26] Ruddlesden-Popper phase. Therefore, this work investigates the mechanisms and the phase stability associated with cobaltite topotactic transformations.…”
Section: Introductionmentioning
confidence: 99%
“…The difference to the theoretically expected magnetic moment of 9 μB/Tb-atom could be due to crystal electric field effects but also indicate strong pinning of the ferromagnetic domains. 42 Indeed, M(H) curves of Tb4Co2C3 measured at 2 K reveal an unusual stair-like behaviour (inset in Fig. 9) which has completely disappeared at 10 K (Fig.…”
Section: Physical Propertiesmentioning
confidence: 93%